Taurine Ameliorates Thyroid Hypofunction and renal injury in L-NAME-Induced hypertensive rats (2018)
There is a growing global interest in hypertension due to its associated complications including renal dysfunction in patients. The thyroid system reportedly regulates renal function in both animal and human. The present study investigated the therapeutic efficacy of taurine on renal and thyroid dysfunctions in hypertensive rats. Hypertension was induced by oral administration of nitric oxide synthase inhibitor, N-nitro L-arginine-methyl-ester (L-NAME), at 40 mg/kg body weight to the male Wistar rats for 14 consecutive days. The hypertensive rats were subsequently treated with either taurine (100 and 200 mg/kg) or reference drug atenolol (10 mg/kg) for another 14 consecutive days. Hypertensive rats showed renal damage evidenced by elevated plasma creatinine and urea levels when compared with normotensive control rats. Furthermore, LNAME-induced hypertensive rats showed decreased circulatory concentrations of thyroid stimulating hormone, thyroxine, triiodothyronine and the ratio of triiodothyronine to thyroxine. The marked decrease in the renal antioxidant enzyme activities and nitric oxide level was accompanied by significant increase in myeloperoxidase activity and biomarkers of oxidative stress in hypertensive rats. Histological examination of kidneys from hypertensive rats revealed congestion of blood vessels, hemorrhagic lesion and disorganized glomerular structure. However, treatment with taurine or atenolol significantly reversed the suppression of thyroid function, ameliorated renal oxidative stress and histopathological lesions in L-NAME-induced hypertensive rats. Taurine may be a useful chemotherapeutic supplement in enhancing renal and thyroid functions in hypertensive patients.